Dynamic Patterns and Persistence of Anticoagulation Therapy in Patients with Venous Thromboembolism in South Korea: A Nationwide Cohort Study - Yoon, Dongwon; Jeong, Han Eol; Choi, Songhwa; Shin, Ju-Young; Bang, Soo-Mee (Thrombosis and Haemostasis, 2023)
Background Venous thromboembolism (VTE) is associated with increased morbidity, mortality, and health care expenditure. However, the comprehensive utilization of anticoagulation therapy in patients with VTE, especially regarding active cancer, in real-world practice remains unclear.Objective To describe the prescription, persistence, and patterns of anticoagulation therapy among patients with VTE stratified according to active cancer.Methods Using Korean nationwide claims data, we identified an incident, treatment-naïve cohort of patients with VTE from 2013 to 2019 and classified them according to the presence/absence of active cancer. We explored the secular trends, treatment patterns (e.g., discontinuation, interruption, and switch), and persistence of anticoagulation therapy.Results There were 48,504 and 7,255 patients without and with active cancer, respectively. Non-vitamin K antagonist oral anticoagulants (NOACs) were the most common anticoagulant in both groups (65.1 and 57.9%, respectively). The prescription of NOACs increased steeply over time, regardless of active cancer, whereas parenteral anticoagulants (PACs) plateaued and warfarin decreased sharply. A heterogeneous pattern was observed between the groups without and with active cancer (3-month persistence was 60.8, 62.9, 57.2, and 3.4%, respectively; 6-month persistence was 42.3, 33.5, 25.9, and 1.2% vs. 9.9%). Median durations of continuous anticoagulant therapy for warfarin, NOAC, and PAC were 183, 147, and 3 days in nonactive cancer patients, and 121, 117, and 44 days in active cancer patients.Conclusion Our findings suggest that there were substantial differences in persistence, patterns, and patient characteristics of anticoagulant therapy based on index anticoagulant and active cancer.
Keywords: venous thromboembolism; anticoagulants; NOACs; treatment patterns; cancer